2008
DOI: 10.1093/ejechocard/jen125
|View full text |Cite
|
Sign up to set email alerts
|

Haemodialysis: effects of acute decrease in preload on tissue Doppler imaging indices of systolic and diastolic function of the left and right ventricles

Abstract: This study shows that both systolic and diastolic TDI velocities of the LV and RV are preload-dependent. However, the lateral mitral annulus is more resistant to preload changes than either the septal mitral annulus or the lateral tricuspid annulus.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
67
2
6

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 82 publications
(85 citation statements)
references
References 31 publications
10
67
2
6
Order By: Relevance
“…Our data are confirmatory in detecting preload sensitiveness of not only transmitral flow Doppler [7,19] but of main tissue Doppler parameters as well [9,20]. Inferior vena cava diameters as expected were significantly modified by dehydration, accordingly to previous studies [17,20,21].…”
Section: Dehydration During Hd Led To Reduction Of All Main Clinical supporting
confidence: 90%
“…Our data are confirmatory in detecting preload sensitiveness of not only transmitral flow Doppler [7,19] but of main tissue Doppler parameters as well [9,20]. Inferior vena cava diameters as expected were significantly modified by dehydration, accordingly to previous studies [17,20,21].…”
Section: Dehydration During Hd Led To Reduction Of All Main Clinical supporting
confidence: 90%
“…Mendes et al (17) reported that pulsed TDI, colour TDI, and speckle tracking imaging provided similar outcomes for the calculation of S and D myocardial operation in clinically stable patients with ESRD on HD for more than 4 months. Interestingly, Drighil and colleagues (11) suggested that systolic and diastolic venticular TDI velocities are load-dependent, and that potent HD treatment may provide insight into determining the onset of diastolic dysfunction in adolescent ESRD patients. Additionally, Fijalkowski et al (14) suggested that mitral annular TDI velocity may offer an optional worthwhile preload-independent marker for evaluating LV D impairment in ESRD.…”
Section: Discussionmentioning
confidence: 99%
“…Because of this, the frequency and severity of LV dysfunction may be grossly underestimated. Therefore, parameters with low sensitivity to loading conditions (load-independent) are clinically relevant (11,16,17). Our current findings suggest that the Em/Am ratio determined from HD patients using TDI may serve as a relatively loadindependent predictor of diastolic function.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations